2006
DOI: 10.1002/elps.200600386
|View full text |Cite
|
Sign up to set email alerts
|

Microchip electrophoresis with wall‐jet electrochemical detector: Influence of detection potential upon resolution of solutes

Abstract: This report studies the electrochemical response of wall-jet detector for microchip electrophoresis (microCE). It shows that in wall-jet configuration, the electrochemical detector operates in coulometric mode and that there is an influence of detection potential upon peak width and therefore upon the resolution of solutes. Upon raising the detection potential from +0.3 to +0.9 V, the resolution between model analytes, dopamine and catechol, increases from 0.63 to 2.90. The reasons for this behavior originate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Identical results were obtained by other researchers [28] using different macroelectrodes (3 mm diameter). This finding can be explained by the fact that amperometric detection in microchip CE with macroelectrodes can be considered as a coulometry because all injected analytes are oxidized [29]. In our experiment we found that 88% of the analytes were oxidized using GCE and 95% using GCE-MWCNTs.…”
Section: Electrochemical Behavior Of Water-soluble Vitamins On Carbonmentioning
confidence: 59%
“…Identical results were obtained by other researchers [28] using different macroelectrodes (3 mm diameter). This finding can be explained by the fact that amperometric detection in microchip CE with macroelectrodes can be considered as a coulometry because all injected analytes are oxidized [29]. In our experiment we found that 88% of the analytes were oxidized using GCE and 95% using GCE-MWCNTs.…”
Section: Electrochemical Behavior Of Water-soluble Vitamins On Carbonmentioning
confidence: 59%
“…In concordance with previous studies [8], a detection potential of 11.2 V was employed. This potential is high enough to warranty that analytes are immediately transformed to their products and analytical signal peak-broadening is not produced [41]. The surfactant MES has been used to dynamically modify the PDMS surface in NaOH solution [42] and is commonly used as a buffer component in CE.…”
Section: Microchip Pretreatmentmentioning
confidence: 99%
“…For an explanation of such an effect, the following consideration should be made. The behavior of the wall-jet detector in microchip electrophoresis is not amperometric, but rather coulometric due to the large dead volume of the wall-jet detector configuration [41]. Therefore, all of the analyte bands, which are injected into the detector volume, are electrochemically transformed.…”
Section: Fundamentalsmentioning
confidence: 99%
“…If the heterogeneous electron transfer rate of the redox species with the electrode is slow, the current after the analyte band reaches the detector is necessarily less than in a system in which the heterogeneous electron transfer rate is fast [42]. Consequently, slow electron transfer results in the tailing of the peaks because the wall-jet detector works in a practically coulometric regime [41] and iEt À1/2 . On the other hand, rapid heterogeneous electron transfer results in sharp peaks with negligible tailing, which consequently results in higher resolution power and higher peak capacity of the whole microchip electrophoresis-electrochemistry system.…”
Section: Fundamentalsmentioning
confidence: 99%